Aplikasi Virtual Character Untuk Simulasi Virtual Map Pada Gedung P Lantai 2 UK. Petra - Pierretio, Steven; Budhi, Gregorius Satia; Gunadi, Kartika (Jurnal Infra, 2016)
Development and competition in Indonesian University is extremely tight. Petra Christian University is also a Universitys with long-standing and well known to many people in Indonesia. Prospective students would like to see more clearly the shape, structure and atmosphere held at the University. Thus someone created a virtual map for Petra Christian University building by using a Head-Mounted Display Oculus Rift to display a simulation of the map Petra Christian University building. But the virtual map that has been created earlier is simply an empty simulation maps that contain only furniture - furniture and does not contain a virtual character, so that the simulation does not have any college atmosphere. So it was decided to implement a virtual character in a map that looks like a real simulation using a rule-based system.In the development of prior research program conducted every object in the form of the building, so hopefully the results obtained could resemble its original state. Giving materials to the models at the Unity are expected match the colors of the original state. Giving collision features intended to make the user cannot penetrate what as original state.Results on this program, the position and shape of character object in the building resemble the original state that existed at Petra Christian University. Time constraints in making become a major factor, so itâs cannot make the character more in detail. The whole room and the character of the building P 2nd floor has been made, there are only a few sections still incomplete, example on the large staircase of the building P and other small parts. Disadvantages of this program require computer high specification enough to run the program. This is because the resulting resolution on this program can be fairly large.